2009
DOI: 10.1074/jbc.m109.033480
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Up-regulates CD36 Expression and Function via Hypoxia-inducible Factor-1- and Phosphatidylinositol 3-Kinase-dependent Mechanisms

Abstract: Neovascular and degenerative diseases of the eye are leading causes of impaired vision and blindness in the world. Hypoxia or reduced oxygen tension is considered central to the pathogenesis of these disorders. Although the CD36 scavenger receptor features prominently in ocular homeostasis and pathology, little is known regarding its modulation by hypoxia. Herein we investigated the role and regulation of CD36 by hypoxia and by the major hypoxia effector, hypoxia-inducible factor (HIF)-1. In vivo, hypoxia mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 69 publications
4
61
0
Order By: Relevance
“…HMVECs transfected with a luciferase reporter plasmid (pGL3-CD36-luc) encoding a 3519 bp sequence of the CD36 gene immediately proximal to the transcriptional start site 12 showed significant basal luciferase activity (Figure 1A) compared to cells transfected with the control pGL3 plasmid. Activity was decreased by over 80% after LPA exposure for 24 hrs ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HMVECs transfected with a luciferase reporter plasmid (pGL3-CD36-luc) encoding a 3519 bp sequence of the CD36 gene immediately proximal to the transcriptional start site 12 showed significant basal luciferase activity (Figure 1A) compared to cells transfected with the control pGL3 plasmid. Activity was decreased by over 80% after LPA exposure for 24 hrs ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the biological importance of CD36 in angiogenesis, little is known regarding how endothelial cell-specific CD36 transcription is regulated or how that might relate to endothelial cell heterogeneity and function. In retinal MVECs, CD36 transcription is up-regulated in response to hypoxia via HIF-1 transcription factor 12 . The antiangiogenic pathway triggered by HIF-1 signaling counteracts hypoxia-driven proangiogenic pathways, providing a “homeostatic brake” to prevent pathological neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…9,17,18 In contrast, although CD36 is broadly and constitutively expressed in microvascular beds, there is surprisingly little known regarding regulation of its expression on MVECs. Mwaikambo et al 19 recently reported that retinal MVEC CD36 expression was up-regulated by hypoxia via the hypoxia-inducible factor-1 transcription factor, suggesting that up-regulation of a natural antiangiogenic pathway may accompany up-regulation of hypoxia-driven proangiogenic pathways, perhaps to provide a "brake" to prevent excess neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LRP1 internalizes aggregated LDL (Llorente-Cortes et al, 2000). Moreover, hypoxia upregulates the expression of CD36 (Mwaikambo et al, 2009), LOX-1 (Crucet et al, 2013) and LRP1 (Castellano et al, 2011a, Cal et al, 2012a. Thus, one or several of these receptors could be involved in the increased uptake of LDL(−) by cardiomyocytes.…”
Section: Discussionmentioning
confidence: 94%